Hincmar of Rheims : life and work - Stone, Rachel; West, Charles, 1979- (Manchester, UK : Manchester University Press, 2015)
Brings together the latest international research on a key medieval writer and thinker.
9 The bishop and the law, according to Hincmar's life of Saint Remigius10 Family order and kingship according to Hincmar; 11 'The praetor does concern himself with trifles': Hincmar, tThe polyptych of St-Rémi and the slave; 12 Hincmar's parish priests; 13 Heresy in the flesh: Gottschalk of Orbais and the predestination controversy in the archdiocese of Rheims; 14 Hincmar, priests and Pseudo-Isidore: the case of Trising in context; Bibliographies; Index.
Includes bibliographical references and index.
In English.
JSTOR
Keywords: Hincmar, -- Archbishop of Reims, -- approximately 806-882.; Catholic Church -- Bishops -- Biography; Hincmar, -- Archbishop of Reims, -- approximately 806-882.; Église catholique -- Évêques -- Biographies; Hincmar, -- Archbishop of Reims, -- approximately 806-882; Catholic Church; Hincmar -- (Archbishop of Reims ; -- approximately 806-882); Église catholique -- Évêques -- Biographies; Church history -- Middle Ages, 600-1500.; Bishops -- France -- Reims -- Biography; Reims (France) -- Biography; Église -- Histoire -- 600-1500 (Moyen Âge); Évêques -- France -- Reims -- Biographies; HISTORY -- Medieval; Bishops; Church history -- Middle Ages; France -- Reims; Évêques -- France -- Reims (Marne) -- Biographies; Église -- Histoire -- Moyen âge.; Reims (Marne) -- Biographies; 600-1500; Biographies; Biographies; Biographies